The Decompensating Pediatric Inpatient Simulation Scenarios - Aisha Davis; Pavan Zaveri (Association of American Medical Colleges, 2010)
Abstract Introduction In July of 2009, Children's National Medical Center (CNMC) Hospitalist and Emergency Department (ED) educators collaborated to create and implement unique simulation scenarios for trainees rotating on the pediatric hospitalist teams. The goal of this educational intervention is to teach, and allow rehearsal of, an approach to the unstable patient across three scenarios. Trainees use this high-fidelity, low-risk simulation to apply targeted clinical reasoning and their initial assessment and management strategies to core clinical problems. The three scenarios included in this resource cover altered mental status and seizure, respiratory distress and anaphylaxis, and refractory status asthmaticus. Methods This resource contains a template, simulator technologist information, scenario progression, and guided discussion for three scenarios of worsening pediatric inpatients. Each case simulation and debriefing is intended to take approximately 30 to 45 minutes. Results Within 6 months of implementation, the monthly simulation scenario series logged over 85 learner encounters at CNMC with uniformly positive evaluations indicating that learners subjectively felt that their competence in the assessment and management of unstable inpatients was improving. Discussion This educational intervention successfully teaches, and allows rehearsal of, an approach to the unstable patient. Simulations such as these provide the opportunity to assess learners' competency with specific skills as long as rubrics for evaluation are created and applied to similar scenarios. As trainees become even more proficient at timely recognition of sick patients, appropriate initial management, education, patient care, and safety outcomes are expected to improve.